The relationship between school administrators’ transformational leadership and standards quality of learners in small-sized schools under Kanchanaburi Primary Educational Service Area Office 4 - Saiyoy, Porntip; Ruamchomrat, Pongsak; Pumklom, Mitparnee (Mahachula Academic Journal, 2023)
The research was to (1) school administrators’ transformational leadership in small-sized schools under Kanchanaburi Primary Educational Service Area Office 4 (2) standards quality of learners in small-sized schools under Kanchanaburi Primary Educational Service Area Office 4 and (3) the relationship between school administrators’ transformational leadership and standards quality of learners in small-sized schools under Kanchanaburi Primary Educational Service Area Office 4. The samples used in the research were 122 teachers in small-sized schools under Kanchanaburi Primary Educational Service Area Office 4, by stratified random sampling according to educational area. The research tool was a scale questionnaire. The research instrument was a 5-level rating scale questionnaire with content validity 0.67-1.00 and reliability 0.95 to collect data which were analyzed in statistical terms of percentage, mean, standard deviation, and Pearson’ product moment correlation coefficient. The findings: (1) School administrators’ transformational leadership in small-sized schools under Kanchanaburi Primary Educational Service Area Office 4, was overall and each aspect at high level. Ranking in the order of mean from high low as ideological influence, inspiration, The aspect of taking into account the individuality and intellectual stimulation. (2) Standards quality of learners in small-sized schools under Kanchanaburi Primary Educational Service Area Office 4, as a whole, the practice was at a high level. When considering each aspect, it was found that the practice was at a high level in all aspects. Sorted by average is the aspect of the academic achievement of the learners, followed by the desirable characteristics of the learners. (3) The relationship between school administrators’ transformational leadership and standards quality of learners in small-sized schools under Kanchanaburi Primary Educational Service Area Office 4, as a whole, it was found that there was a very high level of positive correlation with statistical significance at 0.01